Impact of Lactobacillus paracasei IMC502 in coculture with traditional starters on volatile and non-volatile metabolite profiles in yogurt. (December 2020) - Gu, Yuxiang; Li, Xing; Xiao, Ran; Dudu, Olayemi Eyituoyo; Yang, Lin; Ma, Ying
Graphical abstract: Highlights: The effect of L. paracasei IMC502 on metabolite formation in yogurt was studied. Volatile metabolites accountable for separation were indicated in loading plot. Non-volatile metabolite profiles of yogurts were distinguished by PCA and HCA. 94 discriminatory metabolites were screened by multivariate statistical analysis. Abstract: The impact of Lactobacillus paracasei IMC502 co-fermented with traditional starters on metabolites in yogurt was evaluated using metabolomic analysis. Forty-four volatile metabolites were determined using headspace solid phase microextraction and gas chromatography-mass spectrometry, including alcohols, esters, organic acids, carbonyl and sulfur compounds. Acetaldehyde, diacetyl, acetoin, acetone, butanoic and acetic acid were present in yogurts in higher intensity, which are the major volatile metabolites related to yogurt flavor. L. paracasei IMC502 did not affect the amounts of acetaldehyde, diacetyl and acetoin while promoted the formation of acetone and butanoic acid. A total of 196 non-volatile metabolites including nucleosides, amino acids, carbohydrates, lipids were analyzed using UPLC-Q-TOF-MS. Non-volatile metabolite profiles of these two types of yogurts were distinguished and 94 differential metabolites were screened using multivariate statistical analysis, which were mainly associated with the biosynthesis of secondary metabolites, amino acid metabolism and nucleotide metabolism. The impact of storage on metabolites was also investigated. The amounts of the majority of carbonyl compounds, organic acids and free amino acids increased, while those of acetaldehyde, diacetyl and lactose decreased during storage. This study provides insights into the metabolic mechanism of L. paracasei and represents a real advance in the study of the metabolites in yogurt.